Replication of association of DENND1A and THADA variants with polycystic ovary syndrome in European cohorts. Issue 2 (17th December 2011) - Goodarzi, Mark O; Jones, Michelle R; Li, Xiaohui; Chua, Angela K; Garcia, Obed A; Chen, Yii-Der I; Krauss, Ronald M; Rotter, Jerome I; Ankener, Wendy; Legro, Richard S; Azziz, Ricardo; Strauss, Jerome F; et al.
Abstract : Background: Polycystic ovary syndrome (PCOS) is a complex endocrine disorder with a strong familial component. PCOS is characterised by hyperandrogenaemia and irregular menses. A recent genome-wide association study (GWAS) of PCOS in a Chinese cohort identified three reproducible PCOS susceptibility loci mapping to 2p16.3 (luteinising hormone/choriogonadotropin receptor; LHCGR ), 2p21 (thyroid associated protein; THADA ), and 9q33.3 (DENN/MADD domain containing 1A; DENNDIA) . The impact of these loci in non-Chinese PCOS cohorts remains to be determined. Methods and results: The study tested association with PCOS of seven single nucleotide polymorphisms mapping to the three Chinese PCOS loci in two European derived PCOS cohorts (cohort A = 939 cases and 957 controls; cohort B = 535 cases and 845 controls). Cases fulfilled the National Institute of Child Health & Human Development criteria for PCOS. Variation in DENND1A was strongly associated with PCOS in the study cohort (pcombined cohorts =10 −8 ); multiple variants in THADA were also associated with PCOS, while there was no significant evidence for association of LHCGR variation with PCOS. The present study had >80% power to detect an effect of similar size as was observed by Chen et al for DENND1A and THADA, but reduced power (at <40%) for LHCGR at p=0.0001. The study had sufficient power (57–88%) for LHCGR at p=0.01. Conclusions: At least two of the PCOS susceptibility loci identified in the Chinese PCOS GWAS ( DENND1A and THADA ) are also associated with PCOS in European derived populations, and are therefore likely to be important in the aetiology of PCOS regardless of ethnicity. The analysis of the LHCGR gene was not sufficiently powered to detect modest effects.